Expanding the Mutational Spectrum of CRLF1 in Crisponi/CISS1 Syndrome - Piras, Roberta; Chiappe, Francesca; Torraca, Ilaria La; Buers, Insa; Usala, Gianluca; Angius, Andrea; Akin, Mustafa Ali; Basel-Vanagaite, Lina; Benedicenti, Francesco; Chiodin, Elisabetta; El Assy, Osama; Feingold-Zadok, Michal; et al. (Human mutation, 2014)
ABSTRACT Crisponi syndrome (CS) and cold‐induced sweating syndrome type 1 (CISS1) share clinical characteristics, such as dysmorphic features, muscle contractions, scoliosis, and cold‐induced sweating, with CS patients showing a severe clinical course in infancy involving hyperthermia associated with death in most cases in the first years of life. To date, 24 distinct CRLF1 mutations have been found either in homozygosity or in compound heterozygosity in CS/CISS1 patients, with the highest prevalence in Sardinia, Turkey, and Spain. By reporting 11 novel CRLF1 mutations, here we expand the mutational spectrum of CRLF1 in the CS/CISS1 syndrome to a total of 35 variants and present an overview of the different molecular and clinical features of all of them. To catalog all the 35 mutations, we created a CRLF1 mutations database, based on the Leiden Open (source) Variation Database (LOVD) system (https://grenada.lumc.nl/LOVD2/mendelian_genes/variants). Overall, the available functional and clinical data support the fact that both syndromes actually represent manifestations of the same autosomal‐recessive disorder caused by mutations in the CRLF1 gene. Therefore, we propose to rename the two overlapping entities with the broader term of Crisponi/CISS1 syndrome. Expanding the mutational spectrum of CRLF1 in Crisponi/CISS1 Syndrome Mutations in the CRLF1 gene are responsible for Crisponi/Cold Induced Sweating Syndrome Type 1 (CS/CISS1), a rare autosomal‐recessive disorder characterized by four distinct features, such as hyperthermia and feeding difficulties in the neonatal period, scoliosis, and cold‐induced sweating in the evolutive period. In this study we expanded the mutational spectrum of CRLF1 in the CS/CISS1 syndrome to a total of 35 variants in 56 patients from 47 families. The highest prevalence is found in Sardinia, Turkey and Spain.